Підхід до побудови інформаційної основи системи підтримки прийняття рішень (СППР) по комплексній оцінці інноваційних проектів техногенної безпеки в будівництві - Ізмайлова, О. В.; Красовська, Г. В.; Белявін, Д. О.; Красовська, К. К.; Поліщук, А. Ю. (Ways to Improve Construction Efficiency, 2012)
The work is devoted to creating the informational basis of DSS, which involves the formation of a set of performance criteria making, classification groups, identifying sources of information, approaches and methods to determine their values in terms of different levels of certainty of data.